Students' Perceptions of Using ChatGPT for Academic Writing in English - Peter Launonen; Ekaterina Talalakina; Galyna Dubova (Półrocznik Językoznawczy Tertium)
This article explores the perceptions of university students on the use of ChatGPT for academic writing in English. Participants (n = 79) are all students on mandatory English-language courses at a university Language Centre in Finland. They are predominantly first-year bachelor’s degree students from various degree programmes in different faculties. Participants’ insights were collected via a survey that was administered to several intact groups during the autumn semester of 2023. The survey collected quantitative and qualitative data which were analysed and discussed in light of students’ developing academic writing skills in English. The study sheds light on students’ specific uses of the AI-driven tool as well as their perceptions of its impact on not only the writing process and product, but also on their own writing skills. The results indicated that students perceived ChatGPT to have above average usability, a finding which was supported and elucidated by students’ free responses concerning ways in which they have used this technology. Conversely, the reasons that some students had not used it included, amongst others, a lack of need, ethical concerns and doubts about its usefulness. Given the continued development and availability of large language models such as ChatGPT, this research has clear implications for all stakeholders in higher education. In particular, by illustrating how students utilise ChatGPT in their academic writing, the study provides university language teachers with the insights needed to ensure that their course outcomes, content and assessments remain reflective of students’ developing knowledge and study practices.